Technical and economic evaluation of an engine and irrigation pump using a T-type mixer for natural gas - ElHelew, Waleed Kamel; Abdelmaqsoud, Abdallah Mahmoud; ElBagoury, Khaleed Faran; Shanan, Hayder AbdElHussein (Frontiers in Mechanical Engineering, 2023)
Energy is regarded as one of the most crucial resources in the industrial process. Numerous measurements were made in the year 2021 in the workshops of the Agricultural Engineering Department, Faculty of Agriculture, Ain Shams University, Egypt, using a gasoline engine (single cylinder with air-cooling) that was used to power an irrigation pump with a discharge diameter of 2 inches, which was manufactured in Egypt. To combine natural gas and air before entering the engine, a variety of mixers were created. Four different types of mixers were employed with iron pipes of various sizes: 90° angle T-mixer (T90), 45° angle T-mixer (T45), 30° angle T-mixer (T30), and venture mixer (VM). The engine shift speeds were set at 1,750, 2,300, 2,900, and 3,500 rpm. The water pump was powered by natural gas and gasoline. The findings in this study focused on the evaluation of technical indicators for several types of mixers that combine natural gas and air to power an irrigation pump, where the actual power (braking power) is superior to all types while operating with gasoline (3.07 kW). A commensurability on every side the report of on the up steam, in the mixer type (T45) (2.83 kW) was 7.8% about than gasoline. The lowest specific fuel consumption (S.fc) for gasoline was 219.025 gm/Kw.h at an engine speed of 2,900 rpm. The T45 mixer had the lowest S.fc of 234.612 gm/KW.h, compared with other types of mixers at an engine speed of 2,900 rpm, an increase of 6.6% compared with gasoline. The T45 mixer had the highest pump discharge of 528.133 L/min, an increase of 2.1% compared with gasoline. Compared with other types of T-mixers, the T45 mixer had the highest actual hydraulic power of 0.6 kW, which was 10.5% lower than that of gasoline. As for the economic indicators, the T90 mixer had the lowest net present value (NPV) of 77219.5, and the T45 mixer had the highest NPV of 106900.7. The mixer-type VM had the lowest benefit–cost ratio (B/C) of 1.38, and the T45mixer had the highest B/C of 1.54.